Study of Second Hankel Determinant for Certain Subclasses of Functions Defined by Al-Oboudi Differential Operator (Baghdad Science Journal, 2020)
The concern of this article is the calculation of an upper bound of second Hankel determinant for the subclasses of functions defined by Al-Oboudi differential operator in the unit disc. To study special cases of the results of this article, we give particular values to the parameters A, B and λ